Factors Influencing Risky Actions on Early Adolescent Reproductive Health at Junior High School 30 Kerinci - Mira Eka Putri; Ariadi Ariadi; Yuniar Lestari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Deviations in sexual behavior often occur among adolescents. The development of the current era makes information disclosure through media and electronics have a major influence on adolescent sexual behavior. The research objective was to determine the factors influencing risky actions on the reproductive health of early adolescents at public junior high school 30 Kerinci. This type of quantitative analytic research with a cross-sectional design approach. The research was conducted in November - December 2022 at public junior high school 30 Kerinci with a total sample of 77 people. The sampling technique for this research is total sampling. Data collection using a questionnaire. Analysis of the research data with the chi-square statistical test and multivariate analysis with the binary logistic test. The results showed that there was a relationship between knowledge and risky actions for reproductive health (p=0.001), there was a relationship between attitude and risky actions for reproductive health (p=0.039), there was a relationship between the role of parents and risky actions for reproductive health (p=0.014), there was no relationship between the role of health workers and reproductive health risky actions (p=0.647), there is a relationship between the role of peers and reproductive health risky actions (p=0.027), the dominant factor that has the most influence on reproductive health risky actions in early adolescents in junior high school 30 Kerinci is the knowledge factor (p-value=0.001; POR=16.619). It is suggested that the school activate youth care activity services activities at schools in cooperation with local health workers. It's also suggested that health workers provide health education or youth health seminars at schools to provide information about reproductive health for adolescents. Furthermore, it is suggested to parents of students to control adolescents so that adolescents are correct in receiving health information, especially reproductive health, and seeking information related to adolescent reproductive health together. Keywords : Adolescents, Risky Action , Reproductive Health